Saisir le processus de remémoration organisationnelle - Sylvie Grosjean; Luc Bonneville (Revue d'anthropologie des connaissances)
In this article, we study the process of organizational remembering by mobilizing the Actor-Network Theory (ANT). More specifically, we underline the place and the role played by linguistic (conversation, narrative) and non linguistic (texts, artefacts) forms of mediation in the process of organizational remembering. We show how the creation, production and circulation of knowledge, along with the coordination of actants are at the heart of this process. To do it, we present an empirical research in a 911 dispatch centre in Québec (Canada), focusing on the dynamics of interaction within a workplace.